Implementation of MQTT Protocol on ESP32-Based OEE Analysis Development Board - Amir Akbar Wicaksono; Yuli Kurnia Ningsih; Indra Surjati (Universitas Muhammadiyah Surakarta, 2024)
The transition to Industry 4.0 requires major investments in devices and mechanisms that enable interconnectivity between people, machines, and processes. One important concept related to Industry 4.0 is the so-called Industrial Internet Of Things or IIoT. The application of IIoT in the industrial scope is the measurement of Overall Equipment Effectivness (OEE) through the IoT paradigma. Generally, OEE measurements are carried out manually by production operators on the machine being measured, and data processing is carried out by supervision manually as well to then analyze the OEE value of the machine being measured. In this research, an ESP32-based OEE Analysis Development Board with MQTT protocol is proposed to replace the manual OEE measurement process. The results of direct implementation on the production floor show that the ESP32-based OEE Analysis Development Board with MQTT protocol can be used as an alternative to OEE measurement with a maximum error value on OEE measurement of 16%.